Correction: Tunable deep-blue luminescence from ball-milled chlorine-rich Csx(NH4)1−xPbCl2Br nanocrystals by ammonium modulation. Issue 30 (1st April 2022) - Xiao, Hongfei; Xiong, Hao; Li, Ping; Jiang, Linqin; Yang, Aijun; Lin, Lingyan; Kang, Zhenjing; Yan, Qiong; Qiu, Yu
Abstract : Correction for 'Tunable deep-blue luminescence from ball-milled chlorine-rich Cs x (NH4 )1− x PbCl2 Br nanocrystals by ammonium modulation' by Hongfei Xiao et al., Chem. Commun., 2022, 58, 3827–3830, DOI: ; 10.1039/D1CC07125D .